The contributions of the Pedagogical Residency to the Initial Training of Biological Sciences Teachers: the State of the Question (Research, Society and Development, 2020)
This investigation focuses on the construction of a bibliographic survey, as State of the Question type, to guide a proposal for a dissertation on the training of undergraduate students in a Biological Sciences course included in the Pedagogical Residency Program, especially with the sexuality theme. Thus, this work aims to demonstrate how the State of the Question was built and how it made possible to learn more about research in the initial formation area  with a focus on the Pedagogical Residency and Sexuality Program. To search for works were used: Portal of Journals of the Coordination for the Improvement of Higher Education Personnel (CAPES), the Brazilian Digital Library of Theses and Dissertations (BDTD) and the Proceedings of the 2018 National Meeting of Licentiate Programs (ENALIC). The results showed a diversity of works with different contributions of the Pedagogical Residency in undergraduate courses in Biological Sciences, as well as the theoretical and methodological aspects adopted in the research. All of these results can help with other research similar to the under emphasis in this work.